The copyright dilemma shaping the future of generative AI - Enriquez, Jose Miguelito (2024)
Do Generative Artificial Intelligence models violate copyright law? Tensions between AI developers and copyright holders have risen as courts and government agencies race to answer this question. Whatever the answer may be, it will surely define the future of AI development.